Serotyping And Antibiogram Of E.Coli Isolates Recovered From Bats - Ingle, V.C.; Tembhurne, P.A.; Kamble, S.; Undirwade, S.; Ingle, R.; Bhaisare, D.; Wankhade, G.; Meshram, Y.; Lahade, V.C.; Pawade, M.; Kalorey , D.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Thirty five fecal samples from bats irrespective of breed, age and sex were processed for isolation of enteric bacteria. Out of these, 7 were found positive for E.coli. All the isolates were subjected to hemolysin production, congo red dye binding ability, antibiotic sensitivity pattern and serotyping. One E.coli isolate was found positive for hemolysin production and one could bind congo red dye. The E.coli isolates were found highly sensitive towards ceftriaxone and ciprofloxacin followed by norfloxacin, cephalexin, amoxicillin, gentamycin and chloramphenicol. The isolates were found to be resistant towards oxytetracycline. Out of the 7 E.coli isolates, 2 were untypable and 5 were serotyped as O116 (3) and O13 (2).